2016
DOI: 10.1177/1533034616650778
|View full text |Cite
|
Sign up to set email alerts
|

Can Stereotactic Body Radiation Therapy Be a Viable and Efficient Therapeutic Option for Unresectable Locally Advanced Pancreatic Adenocarcinoma? Results of a Phase 2 Study

Abstract: Stereotactic body radiotherapy is a safe and effective treatment for patients with locally advanced pancreatic cancer with no G3 toxicity or greater and could be a promising therapeutic option in multimodality treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
71
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 26 publications
5
71
0
Order By: Relevance
“…Many groups have quantified OS in their studies evaluating SBRT, but we are unaware of any to date that have directly compared the survival outcomes of SBRT versus CFRT (6,9,12,21,22). The enhanced survival observed in our study might be explained by the high rates of LC (~72% at 1 year) afforded by dose escalation seen with SBRT (20,23,24). Improved LC is perhaps associated with better OS as LC addresses the modest portion of individuals who die specifically from local disease (25,26).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Many groups have quantified OS in their studies evaluating SBRT, but we are unaware of any to date that have directly compared the survival outcomes of SBRT versus CFRT (6,9,12,21,22). The enhanced survival observed in our study might be explained by the high rates of LC (~72% at 1 year) afforded by dose escalation seen with SBRT (20,23,24). Improved LC is perhaps associated with better OS as LC addresses the modest portion of individuals who die specifically from local disease (25,26).…”
Section: Discussionmentioning
confidence: 80%
“…Our analysis also exposed several positive prognostic factors for OS such as diagnosis after 2010, lower comorbidity score, younger age, tumor size <3 cm, nodal stage zero, and receipt of chemotherapy (P<0.05). Several of these factors have already been discussed in the literature (3,(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of advanced XRT techniques and procedures such as breath-hold, real-time tumour tracking, respiratory motion reconstructions and soft tissue matching have allowed dose escalation to be safely administered. SBRT further refines the target conformality of XRT to feasibly deliver a higher Biologically Effective Dose (BED) in a shorter period in order to improve LC for LAPC patients from 79% to 94%, translating to an increased OS [3,[36][37][38][39][40]. The SBRT chemoradiation trial results summarised in Table 2 are difficult to compare and interpret between studies due to the diversity of fractionation schemes, recording of statistics and inhomogeneity of recruited patients (e.g., respectability and disease status).…”
Section: Stereotactic Body Radiation Therapymentioning
confidence: 99%
“…Previously, larger target margins (median planning target volume of 136 cm 3 ) encompassed more of the duodenal mucosa and increased number of fields resulted in higher incidence of late grade ≥ 2 GI toxicities (up to 94% in Hoyer, et al's [47] multi-fraction SBRT study) [41]. More recently Chuong, et al's [37] and Comito, et al's [40] fractionated SBRT studies demonstrated a lower incidence of acute toxicities (grade 3 ≥ 0) for median planning target volumes of (111.01 and 64.7 cm3, respectively) paired with a high 1-year LC (≥ 81%) and MST (15 and 19 months, respectively) for LAPC patients.…”
Section: Stereotactic Body Radiation Therapymentioning
confidence: 99%
“…Stereotactic body radiation therapy (SBRT), an advanced radiotherapy technique delivering ablative doses of radiation in a few fractions, could, due to the tight margins used during treatment delivery, potentially minimize the toxicity of normal surrounding tissues. Also, due to the small number of treatments used when delivering SBRT, its use would minimize interruptions in chemotherapy delivery [17], and data supports its use in select cases for patients with unresectable pancreatic cancer [18,19]. While several single institution studies have reported that SBRT is an attractive neoadjuvant option with margin negative resection rates above 90% and improved survival with mild radiation toxicities [20], there is currently insufficient data to recommend it as a standard treatment regimen.…”
Section: Introductionmentioning
confidence: 99%